Rekonstruksi Supervisi Pendidikan Berbasis Kecerdasan Emosional Kepala Sekolah (Studi Kasus di SMK Nurul Haromain Pujon Malang) - M. Fikri Zaki; Akhmad Fauzi Hamzah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to reconstruct a model of educational supervision based on the emotional intelligence of school principals within the context of vocational secondary schools (SMK). The research is grounded in the observation that current supervision practices remain predominantly administrative and lack emotional engagement, despite the fact that effective supervision largely depends on the quality of the relationship between principals and teachers. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation. Research subjects include the school principal, vice principals, and teachers at SMK Nurul Haromain Pujon, Malang Regency. The findings indicate that the principal has demonstrated various dimensions of emotional intelligence—such as empathy, self-regulation, and interpersonal communication—within supervision practices, although not yet through a structured framework. Emotional intelligence significantly contributes to improving teacher motivation, discipline, and the overall health of workplace relationships. Based on these findings, a conceptual model of emotionally intelligent supervision is proposed, consisting of three stages: emotional diagnosis, reflective dialogue, and collective action. This model is more personal, adaptive, and empowering, and is considered more suitable for the vocational school context, especially those with strong religious values. The results are expected to serve as an alternative model for more humanistic and contextual educational supervision practices in Indonesia.